Mask Wearing as Cultural Behavior: An Investigation Across 45 U.S. States During the COVID-19 Pandemic - Kemmelmeier, Markus; Jami, Waleed A. (Frontiers in Psychology, 2021)
Facial coverings, conventionally referred to as “masks,” are a prime tool in fighting airborne pathogens. Yet, during the COVID-19 pandemic in the United States the use of masks encountered acceptance and resistance based on existing patterns of cultural division and polarization. We argue that mask wearing must be understood on the basis of existing cultural frames assessed at both the individual-level and the U.S. states. We relied on three prominent frameworks in cultural psychology: individualism-collectivism, which we applied in terms of state-level differences as well as independent and interdependent self-construals; the tightness-looseness framework, which allowed us to examine between-state differences, as well as research on U.S. honor cultures. With mask wearing having been politicized during the early phase of the crises, we also examined political orientation as a predictor. We generated hypotheses concerning mask wearing behavior, perceptions of utility, subjective experiences, and the various social meanings attributed to masks. Our data of 633 participants from 45 U.S. state were analyzed using a series of multilevel models, controlling for demographics and state-level wealth. Conservatism emerged as a predictor most consistently associated with unfavorable perceptions of mask wearing, and the only cultural variable associated with lower likelihood of mask wearing. Collective interdependence predicted favorable mask perceptions, in part because mask wearing behavior was considered normative. Independent self-construal was linked to greater intent to wear masks, and even though highly independent individ¬uals said they disliked wearing masks, dislike had no implications for wearing masks. Partici¬pants from tightener (vs. looser) states wore masks as a means of protecting others, had better mental health when wearing masks, believed mask wearing to be both necessary and a civic duty, and trusted the officials’ handling of COVID-19. Conversely, participants from U.S. honor states were more likely to regard masks as a sign of weakness and also perceived masks to be socially isolating. Our discussion focuses on the cultural and political context of mask wearing, argues that different communities in the U.S. respond on its symbolic and social meaning, and discuss suggest strategies to increase mask wearing among those who are reluctant.